1996
DOI: 10.1007/bf02523928
|View full text |Cite
|
Sign up to set email alerts
|

Identification of adulterants in olive oils

Abstract: The application of discriminant analysis for identifying and quantifying adulterants in extra virgin olive oils is presented. Three adulterants were used (sunflower oil, rapessed oil, and soybean oil) and were present in the range 5–95%. Near‐infrared spectroscopy and principal components analysis were used to develop a discriminant analysis equation that could identify correctly the type of seed oil present in extra virgin olive oil in 90% of cases. Partial least squares analysis was used to develop a calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 5 publications
0
34
0
1
Order By: Relevance
“…A similar approach was used to determine sunflower oil, rapeseed oil, and soybean oil adulteration in extra-virgin olive oil. 20 In the above two applications, the classification and determination of the degree of adulteration were carried out using the firstderivative spectral profiles. The samples were prepared as adulterations by these oils in 5% steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was used to determine sunflower oil, rapeseed oil, and soybean oil adulteration in extra-virgin olive oil. 20 In the above two applications, the classification and determination of the degree of adulteration were carried out using the firstderivative spectral profiles. The samples were prepared as adulterations by these oils in 5% steps.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy in the prediction of adulteration in controlled experiments with one olive oil and one adulterant reported in the literature varied from 1.72 to 4.15%. Wesley et al 3,20 showed that they could predict adulteration with an accuracy of 4.15%. Yang and Irudayaraj determined the adulteration of olive pomace oil in extra-virgin olive oil with an accuracy of 1.72%, and Tay et al 16 predicted the adulteration of sunflower oil in olive oil with an accuracy of around 2%.…”
Section: Introductionmentioning
confidence: 99%
“…Ramachandraiah et al (14) have reported a test for detection of neem oil (0.5%) in other oils by observing the change in colour of a thin copper strip on heating at 200 . Number of instrumental tech-niques such as thin layer chromatography (TLC), nearinfrared spectropscopy (NIR), differential scanning colorimetry (15)(16)(17)(18)(19)(20) etc. are available for the detection of adulteration of olive oil and butter.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods applied in the examination of chemical composition include the determination of fatty acid profiles by gas liquid chromatography (Firestone et al 1988), high-pressure liquid chromatography (Cortesi 1993;Mariani & Fedeli 1993), pyrolysis mass spectrometry (Goodacre et al 1993), measurement of iodine values and many other determinations. Rapid, non destructive spectroscopic methods such as Raman (Davies et al 2000), ultraviolet (Calapaj et al 1993), MID-IR (Lai et al 1995;Dupuy et al 1996;Guillen & Cabo 1999;Küpper et al 2001) and NIR (Wesley et al 1995;Bewig et al 1994;Sato 1994;Wesley et al 1996;Hourant et al 2000) have all been applied to quantify adulterants in olive oil.…”
Section: Identification and Quantification Of Olive Oil Adulterantsmentioning
confidence: 99%